Efecto del tiempo de uso en las condiciones físicas del suelo andino en el departamento de Nariño, Colombia - Volveras Mambuscay, B; Amézquita Collazos, Edgar; Tafur, H (2007)
Using a rainfall simulator (CIAT), changes in the soil loss and some physical properties associated to water movement by effect of the type of use of the soil through the time of use in the following treatments were evaluated: Non intervened soil with 25% slope (control), a pasture for 25 years and 25% slope and cropping wheat-corn (w-c) of 25, 45 and 70 years of use, each one of these last, with 12% and 25% slope in a Inceptisol of the area of reconversión of the wheat crop of Nariño, Colombia (longitude 75º 14´ west, latitude 0.5º 10´ north, 2710 masl, 795 HR, 12ºC). The dynamics of the soil loss and the infiltration processes and movement of the water on the soil surface for simulated rain of 110 mm h-1 showed that the rate of soil loss, was minimum in the control and the pasture and was increased drastically until the 25 years of agricultural use (rotation w-c), time after which diminishes gradually when increasing the time of use of the soil. Of the applied total water sheet, the control and the pasture infiltrate 98,3% and 94% respectively; after 25, 45 and 70 years of agricultural use (rw-c), only 56%, 48% and 35% of infiltration respectively was detected. The change of agricultural use (rw-c) generated increase of the apparent soil density and decrease of the clay percentage and organic matter when increasing the intensity and the time of use of soil.